Van Toledo naar Granada : De Aarde en haar Volken, 1906 - Dieulafoy, Jane, 1851-1916 (Salt Lake City, UT : Project Gutenberg, 2004)
"Van Toledo naar Granada" by Jane Dieulafoy is a historical account likely written in the late 19th century. This work explores the rich cultural and geographical landscapes between Toledo and Granada, highlighting the intricate history and legends tied to the regions of Spain, particularly referencing key historical figures and events along the way. The opening of the book introduces the landscape of Castile, painting it as both a beautiful and stark terrain, heavily influenced by its past and agricultural struggle. Dieulafoy highlights various historical landmarks, like the river Tagus and the city of Toledo, while also discussing the hardships faced by local farmers, the influence of the Mesta, and reflections on the legacy of figures such as Cervantes. It sets the stage for a journey rich in historical context and cultural significance, inviting readers to delve deeper into the storied lands of Spain. (This is an automatically generated summary.)
Release date is 2004-11-28
Produced by Jeroen Hellingman and the PG Distributed Proofreaders Team
Keywords: Spain -- Description and travel